Three-year outcomes related to coronary stenting; a registry-based real-life population study. (3rd May 2020) - Piuhola, J.; Holmström, L.T.A.; Niemelä, M.; Kervinen, K.; Tulppo, M.; Asikainen, R.; Hypèn, L.; Junttila, M.J.
Abstract: Objectives . Developments in medication and coronary interventions have improved coronary artery disease (CAD) treatment. We studied long-term outcomes in an observational, real-life population of CAD patients undergoing percutaneous coronary intervention (PCI) depending on the presentation and the stent type used. Design and results . Register included 789 consecutive patients undergoing PCI. Follow up period was three years with primary composite outcome (MACE) of all cause -mortality, myocardial infarction and target lesion revascularization. Mean age was 65 ± 11 and 69% were male. New-generation drug-eluting stents (DES-2) were associated with lower adjusted rates of MACE (HR 0.47; 95% CI 0.29–0.77) but not mortality (HR 0.50; 95% CI 0.22–1.14) in comparison to bare-metal stents. Patients with STEMI (14.4%) or NSTEMI (13.7%) had higher crude mortality rates than those with unstable (4.5%) or stable CAD (3.1%; p  < .001). The association diminished after adjustments in NSTEMI (HR 2.01; 95% CI 0.88–4.58). Among smokers 45% quitted and 36% achieved recommended cholesterol levels. Conclusions . The overall prognosis was good. Irrespective of comorbidities, NSTEMI was not associated with worse outcome than stable CAD. DES-2 was associated with lower rates of MACE than BMS without affecting mortality rate. Patients succeeded better in smoking cessation than reaching recommended cholesterol levels.